Edukasi Sadar Hukum Mengenai Bahaya Judi Online dan Pinjaman Online Ilegal di Kalangan Remaja di SMK Pariwisata Anyer - Siti Hanan; Fathurohman Fathurohman; Tubagus Faisal; Sri Mulyati; Solihat Solihat; Mumtaz Fahmi Ismail; Melita Sugiarti (Jurnal Kabar Masyarakat, 2024)
This research aims to provide education about legal awareness at the Anyer Tourism Vocational High School (SMK) in an effort to prevent the practice of online gambling and illegal online loans among teenagers, as well as to understand the legal impacts that teenagers involved in these activities may face. Through legal education activities regarding online gambling, this is one form of effort to provide education to students at Anyer Tourism Vocational School. In this community service, the author uses methods of presentation and discussion regarding the prevention and handling of online gambling and illegal online loans. The specific target of this service is that the students of Anyer Tourism Vocational School can be well educated regarding understanding, understanding, legal basis and efforts to prevent and overcome cases of online gambling and the risks of making illegal online loans. The main aim of holding this activity is to make students aware of the dangers of online gambling and that illegal loans are very vulnerable to risk. The risk of online gambling addiction is that students will not focus on their lives and if the perpetrator does not have the money to play online gambling, the result is that online gambling players will look for illegal loans to be able to continue playing online gambling.